2003
DOI: 10.1021/om030584o
|View full text |Cite
|
Sign up to set email alerts
|

Metallathiirenes. 5.1 Bis- and Tris(methimazolyl)borato Thiocarbamoyl Complexes of Molybdenum(II)

Abstract: Thiocarbamoyl complexes [Mo(η2-SCNMe2)(CO)2{H n B(mt)4 - n }] (n = 1, 2) are obtained from the reactions of [Mo(η2-SCNMe2)Cl(CO)2(tmeda)] and Na[H n B(mt)4 - n ] or via reactions of the salts Na[Mo(CO)2+ n {H n B(mt)4 - n }] with Me2NCSCl. For n = 2, the complex displays agostic B−H−Mo coordination in both solution and the solid state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 25 publications
3
8
0
Order By: Relevance
“…In 1-IM , the boron atom bridges to Ni–H b Bond, where the Ni–H a distance is 1.473 Å, and the B–H a and B–Ni distances are 1.363 and 2.397 Å, respectively. Such pyramidal intermediates, in which the boron Lewis acid binds to the M–H bond and the M–(μ 2 -H)–B orients in the metal d z 2 orientation, have been observed previously in related systems. This cis dihydride Ni II intermediate is less stable than RC by 27.4 kcal/mol.…”
Section: Resultssupporting
confidence: 68%
“…In 1-IM , the boron atom bridges to Ni–H b Bond, where the Ni–H a distance is 1.473 Å, and the B–H a and B–Ni distances are 1.363 and 2.397 Å, respectively. Such pyramidal intermediates, in which the boron Lewis acid binds to the M–H bond and the M–(μ 2 -H)–B orients in the metal d z 2 orientation, have been observed previously in related systems. This cis dihydride Ni II intermediate is less stable than RC by 27.4 kcal/mol.…”
Section: Resultssupporting
confidence: 68%
“…The related complex [Au(PPh 3 ){HB(mt t Bu ) 3 }] has even shorter B−H···Au separations (2.450−2.489 Å) . Complex 1 results from the reaction of Na[H 2 B(mt) 2 ] and either [Au(NO 3 )(PPh 3 )] or [AuCl(PPh 3 )] . In contrast, Reglinski and Spicer have reported that the reaction of Li[PhB(mt) 3 ] with [AuCl(PEt 3 )] affords [Au(PEt 3 ){PhB(mt) 3 }] ( 2 ), in which the potential chelate coordinates to gold through a single sulfur donor .…”
Section: Resultsmentioning
confidence: 99%
“…The positive ion FAB mass spectrum revealed the presence of an ion corresponding to [Au 2 (PEt 3 ) 2 {H 2 B(mt) 2 }] + , and accordingly the negative ion ESI mass spectrum was also measured and found to contain an isotopic cluster consistent with the decarbonylated bimetallic “[Mo 2 {H 2 B(mt) 2 }] − ” fragment. The 1 H NMR spectrum of the product also included a broad resonance at δ H = −4.18, in an area characteristic of (mt) x B−H−Mo three-center, two-electron ineteractions, ,,, though this could not be integrated with precision. A crystallographic study of the product, the results of which are summarized in Figures and , revealed it to be the unusual salt [Mo 2 {μ-H 2 B(mt) 2 }(CO) 7 ][Au 2 {μ-H 2 B(mt) 2 }(PEt 3 ) 2 ] ( 4 ), in which one H 2 B(mt) 2 ligand has transferred completely from gold to bridge two molybdenum centers, while the remaining gold fragment coordinates to a second equivalent of 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For complexes of group VI metals and the pyridine-2-thiolate ligand, see: Baker et al (1995); Cotton & Ilsley (1981). For related structures of thiocabamoyl-molybdenum complexes, see: Anderson & Hill (1993); Foreman et al (2003); Lim et al (2005). For bond lengths in molybdenum-carbonyl complexes, see: Yih & Lee (2008) and references therein.…”
Section: Related Literaturementioning
confidence: 99%